2022
DOI: 10.1115/1.4053740
|View full text |Cite
|
Sign up to set email alerts
|

Boeing 737-400 Passenger Air Conditioner Control System Model for Accurate Fault Simulation

Abstract: This paper is a continuation of the authors' work on the development of a systematically derived PACK simulation for accurate fault diagnostics, utilising a model-based approach. In practise the PACK simulation accuracy is dependent on a number of factors, which include the understanding of its control system. This paper addresses this by taking an in-depth look at the factors controlling the operation of the PACK in order to enable the gap between the theoretical understanding of the PACK and the engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 5 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The mixing of TCV air is controlled to match the PACK outlet temperature against the cabin demand. In references [8,9] authors have thoroughly reported the functionality of the PACK and its operation under various operating modes, including the control system. The focus of this paper is on the ACM functionality and evaluation of its degradation at the component level.…”
Section: Description Of Ecs Packmentioning
confidence: 99%
See 2 more Smart Citations
“…The mixing of TCV air is controlled to match the PACK outlet temperature against the cabin demand. In references [8,9] authors have thoroughly reported the functionality of the PACK and its operation under various operating modes, including the control system. The focus of this paper is on the ACM functionality and evaluation of its degradation at the component level.…”
Section: Description Of Ecs Packmentioning
confidence: 99%
“…Based on the the findings conceived from the evaluation of degradation in the PACK primary heat exchanger, secondary heat exchanger, ram inlet, TCV, and PV reported by the authors in [8,9], and with the results reported herein for the ACM. The formulation of arobust PACK system-level diagnostics can be implemented to formulate a through-life maintenance approach for the PACK, like the one demonstrated by the authors in Ref.…”
Section: Turbine Efficiency Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cabin temperature demand can be regulated through the input dials mounted on the P5 overhead panel within the cockpit [21]. On the B737-400 aircraft, the cabin temperature demand can be regulated within the range of 18C to 30C.…”
Section: Pack Temperature Controlmentioning
confidence: 99%
“…and will only open once the initial control loop between the PACK controller and the WS o sensor is completed [21]. As shown in Figure 9(b), when the PACK is switched on, the measured pTCV mass flow peaks and then gradually reduces.…”
Section: Temperature and Pressure Measurementsmentioning
confidence: 99%